Alcohol use and personality change in middle and older adulthood: Findings from the Health and Retirement Study. Issue 6 (14th February 2018) - Luchetti, Martina; Terracciano, Antonio; Stephan, Yannick; Sutin, Angelina R.
Abstract: Objective: Personality is known to predict alcohol consumption, but how alcohol use is related to personality change is less clear, especially at older ages. The present study examined the effects of level of alcohol consumption and history of dependence on change in the Five‐Factor Model personality traits in a national cohort of Americans aged over 50. Method: Over 10, 000 adults who participated in 2006–2008 waves of the Health and Retirement Study reported on personality and alcohol use and were followed over 4 years. Results: Latent difference score models indicated decreases in Extraversion to be attenuated for individuals categorized as light‐to‐moderate drinkers at baseline, whereas decreases in Conscientiousness were accentuated by having experienced alcohol dependence symptoms. Moreover, personality difference scores correlated with changes in the amount of alcohol consumed at follow‐up. Conclusions: The findings suggest that patterns of alcohol consumption are associated with changes in personality across the second half of the life span.